Rhizobium as a crop enhancer and biofertilizer for increased cereal production - Mia, Md. Abdul Baset; Shamsuddin, Zulkifli (Academic Journals, 2010)
Greater production of cereals brings forth higher production cost and pollutes the soil environment due to excessive use of chemical fertilizers. Therefore, crop scientists are exploring an alternative source namely biofertilizers which are cost effective and environment friendly. In the biofertilizer technology, Rhizobium-legume is most common and widely used in different countries. Recently, it is also found that rhizobia can make an association with graminaceous plants such as rice, wheat, maize, barley millets and other cereals some time as endophytic without forming any nodule-like structure or causing any disease symptoms. Increasing the ability of rhizobia in biofertilizer, crop enhancing activity in non-legumes especially cereal grains would be a useful technology for increased crop yields among resource-poor farmers. Recent findings showed both more crop enhancing and biofertilizer attributes in cereal crops due to rhizobial inoculation. In addition, plant nutrients like P, K, Ca, Mg and even Fe accumulation were also observed. Therefore, further research in this area will be able to develop a sustainable biofertilizer technology for greater and environment friendly cereal production system.